Indikator Fundamental Ekonomi Pulau Kalimantan: Analisis Tipologi Daerah - Firman Firman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Abstract−The economic development of the island regions often results in inequality both in terms of population and relatively large unemployment, inadequate infrastructure, and inadequate education and health facilities and infrastructure. The purpose of this study was to determine the regional typology of the island of Kalimantan in terms of regional economic fundamental indicators by using secondary data from the provinces of West Kalimantan, South Kalimantan, North Kalimantan, East Kalimantan and Central Kalimantan using regional typology analysis with a research period of 2015-2020 sourced from the National Agency of Drug and Food Control. Center for Statistics. The results of this study found that the island of Kalimantan has a fairly high inequality, although from 2015-2020 the Gini ratio has increased, besides that it is also seen from the typology of the five provinces in Kalimantan that none of them has economic growth, GRDP per capita and HDI/ Together, HDI has a high value, meaning that there are regions with high economic growth and GRDP, but low HDI/HDI and vice versa. North Kalimantan is an area with a fast-developing and fast-growing category because it has a high value of economic growth and per capita income, East Kalimantan which has advanced and fast-growing regional qualifications, namely those with high incomes, followed by HDI, Central Kalimantan and North Kalimantan are included. the category of potential areas or developed regions on the edge of depression or areas with high economic growth but low HDI.